Optimalisasi Potensi Lokal Desa Basseang melalui Inovasi Produk Saus Cabai dan Digital Marketing - Nursyawal Nacing; Wilda Widiawati; Cennawati Cennawati (Pusat Riset dan Inovasi Nasional, 2025)
Leveraging local village potential through product innovation and digital marketing strategies is a strategic approach to supporting the economic independence of rural communities. This Community Service Program (PKM) aims to optimize the abundant chili commodities in Basseang Village by developing innovative chili sauce products based on local potential. This program is implemented through a participatory approach involving the